53.6k views
3 votes
Enter a number in each blank M(x)=(2x-6)(x-4) true statements when M(x)=0 when x=

User Girrafish
by
5.0k points

1 Answer

1 vote

Answer:

{3, 4}

Explanation:

"M(x)=(2x-6)(x-4) true statements when M(x)=0 when x= ?" asks us to find the "roots" of M(x); that is, the x values at which M(x) = 0. Thus, we set

(2x - 6)(x - 4) = 0, which is equivalent to 2(x - 3)(x - 4) = 0.

Thus, x - 3 = and x = 3; also x - 4 = 0, so that x = 4.

The roots of M(x) are {3, 4}

Using the language of the original problem: "true statements when M(x)=0 when x=" the correct results, inserted into the blanks, are x = 3 and x = 4.

User Ansar
by
5.6k points